SEROTYPES AND ANTIMICROBIAL SUSCEPTIBILITY OF NASOPHARYNGEAL PNEUMOCOCCI ISOLATED FROM CHILDREN IN 2010–2016: A RETROSPECTIVE COHORT STUDY - Nikolay A. Mayanskiy; Natalia M. Alyabieva; Olga A. Ponomarenko; Tatiana V. Kulichenko; Inga V. Artemova; Anna V. Lazareva; Ekaterina A. Brozhozovskaya; Olga V. Shamina; Lyubovj K. Katosova (Вопросы современной педиатрии)
Background. Pneumococci (Streptococcus pneumoniae) represent major pathogens that cause acute infections in children. Objective. Our aim was to analyze dynamics of the distribution of nasopharyngeal pneumococcal serotypes and their antimicrobial susceptibility in children. Methods. A retrospective cohort study was conducted. We examined nasopharyngeal pneumococci isolated from children getting care at the National Medical Research Center of Children’s Health (Moscow) in 2010–2016. Serotyping was performed using specific antisera and/or by molecular typing employing PCR. Susceptibility to oxacillin (OXA), erythromycin (ERY), clindamycin (CLI), trimethoprim/sulfamethoxazol, chloramphenicol and tetracycline was tested by the disk diffusion method. In 2013–2016, penicillin (PEN), amoxicillin (AMX), ERY and CLI minimal inhibitory concentrations (MIC) were measured. Results. A total of 1,111 pneumococcal isolates were examined; the sample was obtained from children with a median age of 4 years (P25–P75, 2.4–6.5 years). We identified 48 pneumococcal serotypes; six leading serotypes were serotypes 3, 6А, 6В, 14, 19F and 23F aggregating a proportion of 63.2% in the overall distribution. From 2010 to 2016, the distribution of serotypes has not changed. Wherein, 13-valent pneumococcal conjugate vaccine covered 74% of serotypes in children under 5 years. The five leading serotypes (6А, 6В, 14, 19F, 23F and serotype 19A) had the highest resistance rate. Within 2010–2016, the proportion of OXA- and ERY-resistant pneumococci grew from 21.3% to 35.9% and from 24.5% to 36.9%, respectively. The majority (81.3%) of ERY-resistant isolates possessed an MLSB-phenotype, i. e. were resistant to macrolides, lincosamides, and streptogramin B. In 2013–2016, the rate of PEN- and AMX-resistant pneumococci was 34.6% and 3.5%, respectively. Conclusion. Within the seven year study period, no major shifts in the nasopharyngeal pneumococcal serotype distribution were observed. The pneumococci remained highly susceptible to AMX, but activity of macrolides was significantly reduced. Considering the leading mechanism of macrolide resistance, the use of any macrolides or lincosamides for empiric treatment of pneumococcal infections in children is questionable.